The reconfiguration of Hebrew in the hellenistic period: proceedings of the Seventh International Symposium on the Hebrew of the Dead Sea Scrolls and Ben Sira at Strasbourg University, June 2014 - Joosten, Jan; Machiela, Daniel A.; Rey, Jean-Sébastien (Studies on the texts of the desert of Judah, 2018)
Front Matter -- Copyright page -- Preface /Jan Joosten , Daniel Machiela and Jean-Sébastien Rey -- The Clause “The Lord is a Man of War” (ה׳ אִישׁ מִלְחָמָה) and its Reflexes throughout the Generations /Moshe Bar-Asher -- Tense Forms and Time Frames in Qumran Hebrew Prose and Poetry /Mats Eskhult -- Gutturals and Gemination in Samaritan Hebrew /Steven E. Fassberg -- Writing a Descriptive Grammar of the Syntax and Semantics of the War Scroll (1QM)—Laying the Groundwork /Robert D. Holmstedt -- Diachronic Exceptions in the Comparison of Tiberian and Qumran Hebrew: The Preservation of Early Linguistic Features in Dead Sea Scrolls Biblical Hebrew /Aaron D. Hornkohl -- Late Biblical Hebrew and Qumran Hebrew: A Diachronic View /Jan Joosten -- The Hebrew of Tobit in 4Q200: A Contextual Reassessment /Daniel Machiela -- תכמי בשר “Body Parts”: The Semantic History of a Qumran Hebrew Lexeme /Noam Mizrahi -- Linguistically Significant Variants in Qumran Fragments of Psalms /Takamitsu Muraoka -- Rhetorical Markers in A Fortiori Argumentation in Biblical and Post-Biblical Hebrew /Tzvi Novick -- The Etymology of זעטוט “Youth, Young Man” /Gary A. Rendsburg -- Is the Hebrew of the Cairo Genizah Manuscripts of Ben Sira Relevant for the Study of the Hebrew of the Hellenistic Period? /Jean-Sébastien Rey -- Reflections on Orthography and Morphology in Ben Sira’s Hebrew: The 3ms Heh Pronominal Suffix /Eric D. Reymond -- Ṣade—Shin Change in the Dead Sea Scrolls /Alexey Eliyahu Yuditsky and Chanan Ariel -- Back Matter -- Index of Modern Authors -- Index of Ancient Sources.